Screw osteosynthesis of transverse fracture of the patella in children - Simon Oksbjerre Mortensen; Anne Mette Stausholm; Rikke Thorninger (BMJ Publishing Group, 2019)
Objective Patella fractures in children are rare, with an incidence of less than 1% of all pediatric fractures. Literature describes different surgical techniques and outcomes, but there is not a specified superior technique for children. The aim of this study is to assess the functional outcome after screw fixation of transverse patella fractures in children.Methods Two boys at 11 years of age were presented with a transverse fracture of the patella within the same week. Open reduction and fixation of the fractured patella with periost sutures and a 4.0 mm titanium screw inserted from the distal fragment. Afterward, the quadriceps expansion was meticulously repaired with sutures.Results The patients could fully weight bear immediately on a fully extended knee in an orthosis. After 4 weeks, radiological healing was obtained. At the 8-week and 6-month follow-up, the modified Hospital of Special Surgery knee score was 100 points in both patients.Conclusion Single screw fixation provides an excellent outcome after 8 weeks with a full range of motion and full weight bearing, providing a faster recovery.